POTENSI DAN KUALITAS BATUBARA DAERAH LIPON-GENDANG KECAMATAN SUNGAI DURIAN, KABUPATEN KOTABARU, KALIMANTAN SELATAN - -, Yuyun Yuniardi (Bulletin of Scientific Contribution, 2006)
Location of research area was in Lipon-Gendang, Sungai Durian District, Kotabaru Residence, Kalimantan Selatan Province, there were into Tanjung Formation which had Coal Bearing Formation.Focused of subject this research was quality and potential of coal, and those have been coal distribution from several coal seam, resources prediction with used USGS methode, and analysis quality of coal from field research sample.There had been potential enough for coal from result of research. And that proved with have four seam were thickly between 0,2 – 3 m, and predicted of resources were 1.403.550 ton, and then quality of coal : calory average 5419,46 cal/gr and sulfur average 1,47 %.